Nuclear fission research using NAND facility at IUAC - Golda Komalan Satheedas; Akhil Jhingan; Sugathan Pullahnhiotan (AAPPS Bulletin)
Abstract The National Array of Neutron Detectors (NAND) at IUAC is one of the big detector arrays used in experiments to study nuclear fission through the measurement of the neutrons emitted during the process. The array is installed at IUAC heavy ion accelerator facility. NAND consists of 100 liquid scintillators mounted on a semi-spherical geometry covering a total of 3.3 $$%$$ % of 4 $$π$$ π solid angle. The 175-cm-long flight path provides good energy resolution of the emitted neutrons, enabling precise measurement of neutron multiplicity for very heavy nuclei. The fission fragment time-of-flight spectrometer coupled with large array of neutron detectors makes it a versatile tool for exploring the properties of nuclear fission using heavy ions from IUAC accelerators. Over the past two decades, several experiments were performed using NAND facility providing valuable information on traditional fission research extending to new mass region. This article reviews overall details of NAND facility and highlights some important research activities carried out at IUAC. The future research possibilities are also discussed.